Observations of asymmetry in contrasting wave‐ and tidally‐dominated environments within a mesotidal basin: implications for estuarine morphological evolution. Issue 15 (28th July 2016) - Hunt, Stephen; Bryan, Karin R.; Mullarney, Julia C.; Pritchard, Mark
Abstract: Tides are often considered to be the dominant hydrodynamic process within mesotidal estuaries although waves can also have a large influence on intertidal erosion rates. Here, we use a combination of hydrodynamic measurements and sediment deposition records to determine the conditions under which observed waves are 'morphologically significant', in which case they influence tidal and suspended sediment flux asymmetry and subsequently infilling over geomorphological timescales. Morphological significant conditions were evaluated using data from contrasting arms in a dendritic mesotidal estuary, in which the orientation of the arms relative to the prevailing wind results in a marked difference in wave conditions, deposition rates and morphology. By defining the morphological significance of waves as a product of the magnitude of bed shear stress and frequency of occurrence, even small (but frequently occurring) winds are shown to be capable of generating waves that are morphologically significant given sufficient fetch. In the arm in which fetch length is restricted, only stronger but rare storm events can influence sediment flux and therefore tides are more morphologically significant over longer timescales. Water depth within this mesotidal estuary is shown to be a critical parameter in controlling morphological significance; the rapid attenuation of short period waves with depth results in contrasting patterns of erosion occurring during neaps and accretion during springs. Copyright © 2016 John Wiley & Sons, Ltd.